Emerging Role of Coronary CT in Non-ST Elevation Acute Coronary Syndrome - Santoso, Jimmy Oi; Proklamartina, Nurnajmia Curie; Christian, Roy (The Indonesian Heart Association, 2021)
NSTEACS is subset of ACS that may present with a wide degree of stenosis from normal vessels to severe obstruction. Identification of which population of NSTEACS that has normal vessels has attracted a great attention. Several trials on non-invasive imaging such as coronary CT have been largely investigated. Current available trials have showed that coronary CT is accurately identify significant stenosis in patients with NSTEACS thus can be used to rule out the disease and reduce the need and duration of unneeded antithrombotic. However, several limitations of the studies has to be taken into account when translating into clinical practice. Nevertheless, current evidence are showing promising results on the role of coronary CT in management of NSTEACS.